Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Berbasis Website dengan Menggunakan Metode TOPSIS - Adeline Debby Christiana; Evangs Mailoa (AITI, 2022)
Company’s employee are the most important part that influences the level progress in company, so the quality of human resources needs improvement. Employee performance assessment is the solution for company. Some existing companies have implemented employee performance assessments but they are done manually so there is a buildup files and can be errors in calculation of assessments. It’s therefore designed a website employee performance assessment system that contains the results of the implementation TOPSIS method. Data is collected using observation, interviews, and library studies. The final result of this study is preference values that will be displayed in rankings. Based on the analysis of user satisfaction obtained a value of 3.58 which is classified in satisfaction so it’s worth using by the user. This resulting employee performance assessment system can be used to make easier for assessors to provide assessments, speed up the assessment process, and reduce file stacking.